Pengaruh Work-Life Balance Dan Lingkungan Kerja Terhadap Kinerja Karyawan Pada PT Oceanica Megah Utama - Nurmala, Syifa; Yusuf, Faif (Jurnal Mnajemen | Ekonomi | Akuntansi, 2025)
This study aims to determine the effect of Work-Life Balance and Work Environment on Employee Performance at PT Oceanica Megah Utama. This research uses a quantitative approach with a survey method using questionnaires and a Likert scale. The sample consists of all production employees, totaling 51 respondents. Data were analyzed using SPSS version 25 through validity tests, reliability tests, classical assumption tests, multiple linear regression, t-tests, F-tests, and coefficient of determination. The results indicate that both Work-Life Balance and Work Environment have a positive and significant effect on Employee Performance, both partially and simultaneously. The findings suggest that companies should continuously improve policies supporting Work-Life Balance and create a conducive work environment to enhance overall productivity and performance.